2011
DOI: 10.1111/j.1469-7610.2011.02520.x
|View full text |Cite
|
Sign up to set email alerts
|

The mutual prospective influence of child and parental post‐traumatic stress symptoms in pediatric patients

Abstract: This study highlights the long-term influence of parental PTSS on the child's recovery after trauma and calls for a family systems approach and for early interventions in the treatment of traumatized pediatric patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
143
1
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(157 citation statements)
references
References 25 publications
9
143
1
4
Order By: Relevance
“…To our knowledge, this had not been reported before in preschool injured children. Our findings were consistent with a study on school-aged children and their parents after a medical traumatic event [27], but differed from a Each parent could describe more than one concern. Percentages in each cell are expressed as proportions of the total number of participating parents at the respective stages Eur Child Adolesc Psychiatry previous study that only found a relationship between mother-reported child and maternal adjustment after a paediatric burn event [17].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…To our knowledge, this had not been reported before in preschool injured children. Our findings were consistent with a study on school-aged children and their parents after a medical traumatic event [27], but differed from a Each parent could describe more than one concern. Percentages in each cell are expressed as proportions of the total number of participating parents at the respective stages Eur Child Adolesc Psychiatry previous study that only found a relationship between mother-reported child and maternal adjustment after a paediatric burn event [17].…”
Section: Discussionsupporting
confidence: 88%
“…Second, we hypothesised that mothers and fathers would show a moderate to high level of correspondence in terms of their rating of internalising and externalising problem behaviour in the child. Third, in line with a prospective study on school-aged children and their parents after a paediatric medical event [27], we expected a positive relation between parental acute stress and child behaviour problems at 3 and 12 months postburn in mothers as well as in fathers, while controlling for child age, gender, and extent of the burn injury. Fourth, we explored parental worries about the child.…”
mentioning
confidence: 55%
See 1 more Smart Citation
“…Parents often witness the burn accident and subsequently accompany the child through painful wound care procedures and assist with managing the burn wound at home, all of which can influence stress levels [21]. The relationship of parent distress and the impact on child distress is well-researched with numerous studies reporting that a child's distress can be influenced by parents' responses to the traumatic event [23,98,99]. Studies have found that parent behaviors related to situational distress and anticipation of child distress can influence the child's response and psychological recovery from a burn injury [23,98,99].…”
Section: Parent Experience Of Pediatric Outpatient Burn Carementioning
confidence: 99%
“…For a child who sustains a traumatic, unintentional injury such as a burn, recovery can be affected by both the experience of the parent and child during treatment, as parental stress reactions are known to impact on the child's own reactions to stressful situations [23,98,99]. Parents of children who sustain burn injuries have been found to display acute stress reactions related to concerns for their child during the acute treatment phase and longer-term potential psychosocial impacts for the child [136].…”
Section: Introductionmentioning
confidence: 99%